EXAMINATION OF ROMANIA'S ROAD NETWORK IN THE LAST 5 YEARS - M. Csipkés; Z. Kertész-Szabó (Annals of the University of Oradea: Economic Science)
The development of transport can be traced back to the Middle Ages. The plants and manufactories involved in the production of products mainly satisfied local needs. Later, however, with the increase in production volume and the saturation of local needs, the production manufactories sought new markets for themselves. In the beginning, the merchants themselves carried out the delivery of the goods, but the work of the merchants was constantly expanding, and thus it became necessary to use transport companies. In our article, we examine the current situation of road transport in Romania in the last 5 years regarding public roads and highways. We examined the length of the roads in Romania and what place it occupies within the European Union.